Language Variety in the South Revisited - Sabino, Robin; Nunnally, Thomas; Bernstein, Cynthia Goldin, 1947- (Book collections on Project MUSE., 2012)
Top linguists from diverse fields address language varieties in the South. "Language Variety in the South Revisited" is a comprehensive collection of new research on southern United States English by foremost scholars of regional language variation. Like its predecessor, "Language Variety in the South : Perspectives in Black and White" (The University of Alabama Press, 1986), this book includes current research into African American vernacular English, but it greatly expands the scope of investigation and offers an extensive assessment of the field. The volume encompasses studies of contact involving African and European languages; analysis of discourse, pragmatic, lexical, phonological, and syntactic features; and evaluations of methods of collecting and examining data. The 38 essays not only offer a wealth of information about southern language varieties but also serve as models for regional linguistic investigation.